Roquin promotes constitutive mRNA decay via a conserved class of stem-loop recognition motifs - Leppek, Kathrin; Schott, Johanna; Reitter, Sonja; Poetz, Fabian; Hammond, Ming C.; Stoecklin, Georg (Cell, 2013)
Tumor necrosis factor-α (TNF-α) is the most potent proinflammatory cytokine in mammals. The degradation of TNF-α mRNA is critical for restricting TNF-α synthesis and involves a constitutive decay element (CDE) in the 3′ UTR of the mRNA. Here, we demonstrate that the CDE folds into an RNA stem-loop motif that is specifically recognized by Roquin and Roquin2. Binding of Roquin initiates degradation of TNF-α mRNA and limits TNF-α production in macrophages. Roquin proteins promote mRNA degradation by recruiting the Ccr4-Caf1-Not deadenylase complex. CDE sequences are highly conserved and are found in more than 50 vertebrate mRNAs, many of which encode regulators of development and inflammation. In macrophages, CDE-containing mRNAs were identified as the primary targets of Roquin on a transcriptome-wide scale. Thus, Roquin proteins act broadly as mediators of mRNA deadenylation by recognizing a conserved class of stem-loop RNA degradation motifs.
Gesehen am 25.01.2022